The Effect of Shopping Experience and Store Design on Customer Satisfaction at Malls in Jakarta - Frans Sudirjo (North Press, 2024)
This study investigates the effect of shopping experience and store design on customer satisfaction at malls in Jakarta. A quantitative research method was employed, involving 70 respondents who provided their perceptions of the shopping experience and store design through a structured questionnaire. The data was analyzed using SPSS version 26, with multiple regression analysis to assess the relationship between the independent variables (shopping experience and store design) and the dependent variable (customer satisfaction). The findings reveal that both shopping experience and store design positively and significantly influence customer satisfaction, with an R-squared value of 0.58, indicating that 58% of the variance in customer satisfaction is explained by these two factors. The results provide valuable insights for mall operators and retailers, emphasizing the importance of enhancing both the shopping experience and store design to improve customer satisfaction.